2017
DOI: 10.1111/edt.12343
|View full text |Cite
|
Sign up to set email alerts
|

Dental trauma prevention with mouthguard in a nose fracturing blow to the face: Case report

Abstract: Orofacial injuries are common in sports activities and may vary in complexity and the tissues involved. Most sports-related trauma occurs when a player hits another player, an object or the ground. This report presents a case of an injury caused by a punchlike blow to the face during a handball college team practice session. The patient suffered a traumatic blow to the left side of the nose and mouth and promptly attended a dentist. After a clinical examination and a CBCT scan, the following injuries were diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…This can be justified due to the roots' shape, bone thickness, position, and inclination in the arch. 4 The authors reported that more severe dental injuries were prevented because the patient was using a MG. This result is in agreement with previous investigations that conclude that the use of any protection is better than nothing, 25 nasal spine fracture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This can be justified due to the roots' shape, bone thickness, position, and inclination in the arch. 4 The authors reported that more severe dental injuries were prevented because the patient was using a MG. This result is in agreement with previous investigations that conclude that the use of any protection is better than nothing, 25 nasal spine fracture.…”
Section: Discussionmentioning
confidence: 99%
“…10 When impacted, the energy absorption of a MG's material is produced by the distortion and recovery of the buccal protective material. 4 The most used test to evaluate the dampening capacity of MGs are experimental impact tests, in which a strain sensor is attached to the surface that will be analyzed and the region is punctually evaluated in several situations. 1,18 This experimental model is important to provide a punctually quantitative view of strain, but disregard other points that are not in contact with the sensor and may present important stresses to understand the mechanical failures during a trauma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contact sports are those in which participants establish direct physical contact with other players or objects, resulting in greater likelihood of trauma and injuries . Dento‐alveolar injuries such as tooth avulsion, fracture, subluxation, and intrusion demonstrate a significant prevalence in recent studies .…”
Section: Introductionmentioning
confidence: 99%